Impact of Fat Replacement by Core-shell Microparticles on Set Type Yoghurts. Study of their physicochemical, textural and microstructural properties - Yonaha, Maria Veronica (2019)
The aim of this study was to investigate the effect of replacing milk fat matter by core-shell microparticles in set type yoghurt. Microparticles were produced by electrostatic deposition of carboxymethylcellulose (CMC) on thermally induced aggregates of β-lactoglobulin (β-lg)n. Laboratory made yoghurts were prepared with: full fat milk (F), low fat milk (L) and low fat milk with CS microparticles (CS). Yoghurts properties (e.g. physicochemical, rheological, textural) were characterized during storage at 4°C. Trials were also conducted in commercial yoghurts taken as references.Water holding capacity (WHC) and elastic modulus (G´) of CS yoghurts resulted similar to commercial yoghurts. Color properties (L*, a*. b*) were slightly altered and showed no significant variation upon time. CS yoghurts behaved as a weak gel as indicated by the higher n values obtained from mechanical spectra and by the lower firmness obtained from texture measurements. Important differences were observed in microstructure. CS yoghurts showed homogeneous aspect with large aggregates and empty spaces. Bacterial growth in CS yoghurts resulted similar to low fat yoghurts. Replacement of milk fat by microparticles would be feasible giving a final product without major differences, at least instrumentally measurable, to commercial yoghurt.